EFFECT OF NET PROFIT MARGIN (NPM), DEBT TO EQUITY RATIO (DER), TOTAL ASSET TURNOVER (TATO), CURRENT RATIO (CR), AND COMPANY SIZE ON PROFIT GROWTH IN HEALTH SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018–2021 PERIOD - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine the effect of net profit margin, debt to equity ratio, total asset turnover, current ratio, and company size on profit growth in health sector companies listed on the Indonesian stock exchange for the 2018–2021 period. This study uses secondary data. The sample technique in this study used purposive sampling. The number of samples obtained were 15 companies. The analytical method of this research uses descriptive analysis and several types of evaluation using the SmartPLS software. From this study it was concluded that only net profit margin has a significant influence on profit growth. While the debt to equity ratio, total asset turnover, current ratio, and company size have positive effect but do not have a significant on profit growth.